A very English hero the making of Frank Thompson - Conradi, Peter J. 1945-
Gentle, modest and handsome, a fine poet, proficient in nine languages, eccentric Englishman Frank Thompson made an unlikely soldier. The elder of two sons of a formidable family of writers, lover of Iris Murdoch, he was an intellectual idealist. This book tells his story.